Ich kann das schon . I Can Already Do That - Breitel, Heide (Heide Breitel Filmproduktion, 2005)
Verzio FF submission In order to understand someone else, we have to enter into dialogue with them. Children suffering from Down's syndrome have difficulties in learning to speak. So how can their parents relate to them and enter into dialogue? The film follows three children suffering from Down's syndrome from spring 2001 to autumn 2002, documenting a phase of their learning process and the joy they have in life.